Off-Label Use of Gastrointestinal Medications in the Intensive Care Unit. (May 2015) - Barletta, Jeffrey F.; Lat, Ishaq; Micek, Scott T.; Cohen, Henry; Olsen, Keith M.; Haas, Curtis E.; ,
Purpose: Determine the level of evidence supporting off-label gastrointestinal (GI) medication use and identify the medication class and indication whereby off-label use was most common. Materials and Methods: This prospective, multicentered observational study evaluated all medication orders written in 37 intensive care units (ICUs) in the United States, over a 24-hour period. All medications classified as "GI" according to a national reference were identified. The class and indication whereby off-label use was most prominent were determined and the level of evidence was described. Results: There were 774 orders from 363 patients and 63% (489 of 774) were considered off-label. Proton pump inhibitors (PPIs) accounted for most of the off-label usage (55% [271 of 489]), followed by laxatives (16% [77 of 489]) and histamine-2-receptor antagonists (H2RAs; 15% [71 of 489]). When prescribed, 99% (271 of 274) of PPIs, 99% (71 of 72) of H2RAs, and 79% (30 of 38) of promotility agents were off-label. Stress ulcer prophylaxis (100% [309 of 309]), GI bleeding (100% [18 of 18]), and gastric motility (88% [30 of 34]) were the most common off-label indications. The most common strength of recommendation and level of evidence for off-label use was indeterminate (58% [282 of 489]) and none (57% [280 of 489]), respectively. Conclusion: The PPIs are the most widely used off-label medications in the ICU. Stress ulcer prophylaxis is the most common indication. The level of evidence supporting off-label GI medication use is poor.